A közvetlen hozzátartozók mentessége a családtagjuk elleni terhelő tanúvallomás kötelezettsége alól jogtörténeti, etikai és jogfilozófiai szempontból - Ruff, Tibor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The primacy of the blood (family) relationship over the relationship between the individual (the citizen) and the state power can be traced back to natural law. In order to protect the values of domestic harmony and the integrity of the family unit, many jurisdictions have been prompted to determine special rules restricting the testimony of family members in criminal proceedings. The family relationship, mentioned as a relative obstacle to the examination of witnesses, whether it existed at the time the offence was committed or at the time of its assessment, constitutes a ground for this immunity. A person who would accuse himself or a relative of having committed a criminal offence may refuse to testify on the matter, even if he has not refused to testify as a relative of the accused. These two relative obstacles have a link in modern and postmodern law, but their historical development is even more interconnected. The exemption from the obligation to testify arising from the partiality of love has been embraced by the legal systems of the greatest and most enduring civilizations, and, if and when this civilization has been organized as a state, has been made a binding legal norm. In so doing, it has also superseded the state's ethical obligation to enforce justice even in cases of crimes against life, thereby expressing its higher value of intimacy in the family, the site of a person’s emotional socialisation, as a means of fulfilling one of the state’s primary functions. This study compares the foundations of Judaism, Christianity, and Roman law within European legal culture (and, as a counter-example, of Chinese law), which have served as historical arguments for the development of rules of testimony for relatives in the era of legal modernisation.